2020
DOI: 10.1016/j.heliyon.2020.e04475
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for knee osteoarthritis using high molecular weight hyaluronic acid conjugated to plasma fibrinogen – interim findings of a double-blind clinical study

Abstract: Objective Osteoarthritis (OA) is a widespread degenerative joint disease leading to progressive loss of function and pain. Available treatments do not provide long-term relief or improvement. This study aimed to assess the safety and efficacy of a novel intra articular supplement, made of high molecular-weight hyaluronic acid (HA) uniquely conjugated to either purified (RegenoGel) or autologous plasma-derived fibrinogen (RegenoGel-OSP), as a long-term treatment for knee OA. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…[39][40][41][42] Here, we have shown that the integration of the NGs with HA-FB hydrogel enabled uptake of endogenous cells in vivo. The hydrogel used was Regenogel™, a hydrogel that previously showed positive results in cartilage defect models [43] and it is clinically proved in Israel as a treatment to relieve pain in osteoarthritis patients [44] and it is approved in Israel for osteoarthritis treatment. Moreover, this hydrogel was previously used to deliver antimiR-221 using lipofectamine as a carrier system [45].…”
Section: Discussionmentioning
confidence: 99%
“…[39][40][41][42] Here, we have shown that the integration of the NGs with HA-FB hydrogel enabled uptake of endogenous cells in vivo. The hydrogel used was Regenogel™, a hydrogel that previously showed positive results in cartilage defect models [43] and it is clinically proved in Israel as a treatment to relieve pain in osteoarthritis patients [44] and it is approved in Israel for osteoarthritis treatment. Moreover, this hydrogel was previously used to deliver antimiR-221 using lipofectamine as a carrier system [45].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is ProCore's RegenoGel® solution that was commercially approved in Israel in 2016 and recently completed their FDA phase 4 clinical trials. RegenoGel® is based on HA that is mixed with purified platelet‐rich plasma‐derived fibrinogen that conjugates to form an injectable gel 70 . In their clinical trials, they have been able to demonstrate that the gel is efficient at treating the symptoms of OA, that is, pain and knee stiffness, for at least 6 months after treatment start, 70 but more detailed studies are required to investigate the long‐term effect and the ability to regenerate cartilage.…”
Section: Applicationsmentioning
confidence: 99%
“…This Special Issue bridging the gap between science and practice in the promotion of exercise and health and in the scientific assessment, study, and understanding of sports performance, sports injury prevention and treatment, exercise for health as non-surgical and nonpharmacological treatments, rehabilitation techniques, adapted physical activity, drugs in sport, and recommendations for training and nutrition. This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Sciences researchers [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Taken together, these articles are…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…This Special issue comprises 3 review articles and 16 original research publications from a number of Sports Medicine and Movement Sciences researchers [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Taken together, these articles are geared toward the advancement of our understanding Sports Medicine and Movement Sciences arena, including: Cognitive function; Brain health; Gait analysis; Biomechanics; Health sciences; Physiology; Physical activity; Occupational health; Musculoskeletal system; Evidence-based medicine; Aerobic threshold; Anaerobic threshold; Maximal oxygen uptake; Neuroscience; Exercise; Physical Activity; Balance; Metastability; Neuromuscular control; Prevention; Rehabilitation; Health Promotion; Anatomy; Health Technology; Three-dimensional motion analysis; Reliability; knee injury; Athletic pubalgia; Cardiology; Women's Health; Female athletes; Applied psychology; Clinical psychology; Paralympic sport; Goalball; Soccer; Cognitive psychology; Quality of life; Disability; Regenerative medicine; Osteoarthritis; Virtual reality; Sensorimotor control; Sports injury prevention; Epidemiology; Public health; Psychology; COVID-19; Pandemic; Quarantine; Home based exercise; IPAQ-SF; Psychological well-being; PGWBI; Nerve injury; Nerve regeneration; Therapeutic exercise; Wearable technologies; Sprint initiation; Step technique; Multi-directional movement; Novel training environments and digital devices; Adherence; Breast cancer; Lifestyle; Public Health and Digital Epidemiology.…”
mentioning
confidence: 99%